Yoga dalam Pernaskahan Nusantara sebagai Daya Tarik Wisata di Bali - Ida Bagus Subrahmaniam Saitya1; Putu Emy Suryanti (UHN IGB Sugriwa Denpasar, 2020)
The development of tourism attraction is the main driver of the tourism sector requires the cooperation of all stakeholders consisting of the public and the government, direct cooperation from the business community and from the private sector. Cultural tourism is one type of tourism that utilizes the development potential of human cultural output as an object of attraction. This type of tour can provide benefits in the socio-cultural field because it can help preserve cultural heritage as the identity of local people who have that culture. The potential for spiritual tourism to be developed in Indonesia, especially Bali because it has a number of suitable destinations. The arrival of tourists to Bali is a specialty for Bali, because generally people know India as the center of world yoga. In Bali, there are many talks about the teachings of yoga, one of which is the sadaṅgayoga teachings contained in the text of Wṛhaspati Tattwa.